Attempted synthesis of a [beta] or [gamma] resorcinyl alcohol - Ryding, William Wallace (Rhodes University, Faculty of Science, Department of Chemistry, 1952)
The ultimate objective of this research is the elucidation of the mechanism of the resorcinol-formaldehyde condensation. Whilst a vast literature has been built up about the phenol- formaldehyde condensation, that of resorcinol has received but scant attention, probably because the high reactivity of resorcinol rendered the following of the condensation extremely difficult. The earliest observation concerning the resorcinol-formaldehyde condensation was due to Baeyer who, in 1872, condensed resorcinol with various aldehydes. When the aldehyde was relatively inactive crystalline compounds were obtalned but with acetaldehyde or formaldehyde a resinous product resulted. In 1892 Caro condensed an excess ot resorcinol with formaldehyde in the presence of dilute hydrochloric acid; the product obtained recrystallised from alcohol as white microsoopic crystals, decomposed without melting at 250Â° and was stated to be bis (2- 4 dihydroxyphenyl) methane ... In decidlng upon the most suitable lines of attack it would seem that a survey of the literature relating to the phenol-formaldehyde concentration which might be expected to be closely related to that of resorcinol, would be of value. Summary of p. 1-5
Keywords: Alcohol -- Synthesis; Resorcinol